Synthesis of new kojic acid based unnatural α-amino acid derivatives. Issue 21 (1st November 2015) - Balakrishna, C.; Payili, Nagaraju; Yennam, Satyanarayana; Uma Devi, P.; Behera, Manoranjan
Graphical abstract: Abstract: An efficient method for the preparation of kojic acid based α-amino acid derivatives by alkylation of glycinate schiff base with bromokojic acids have been described. Using this method, mono as well as di alkylated kojic acid-amino acid conjugates have been prepared. This is the first synthesis of C-linked kojic acid-amino acid conjugate where kojic acid is directly linked to amino acid through a C–C bond.